The interaction of Serratia bacteria and harmonine in harlequin ladybird confers an interspecies competitive edge - Chaowei Zhang; Hang Zhou; Kang He; Yiqi Xiao; Mengyao Chen; Zhangqi Zuo; Runguo Shu; Yuhang Geng; Shuo Jin; Yang Mei; Bingbing He; Fei Li (Proceedings of the National Academy of Sciences, 2025)
The harlequin ladybird, Harmonia axyridis , is a predatory beetle used globally to control pests such as aphids and scale insects. Originating from East Asia, this species has become highly invasive since its introduction in the late 19th century to Europe and North America, posing a threat to local biodiversity. Intraguild predation is hypothesized to drive the success of this invasive species, but the underlying mechanisms remain unknown. In this study, a feeding assay revealed that while harlequin ladybirds survive feeding on seven-spotted ladybird eggs, the reverse is not true. However, seven-spotted ladybirds that had fed on harlequin ladybird eggs were able to survive the feeding assay when treated with penicillin. Microbiome sequencing and whole genome analysis of harlequin ladybird eggs revealed a newly discovered pathogenic bacterium strain named Serratia harmoniae. The median lethal concentration (LC50) of S. harmoniae was found to be 2.1 × 10 5 times higher in the harlequin ladybird compared to the seven-spotted ladybird. The high tolerance observed in harlequin ladybirds was attributed to harmonine, specifically produced in the fat body of this species. Silencing three key genes in the harmonine biosynthesis pathway— Spidey , Sca2 , and Desat— reduced the production of the compound, leading to increased S. harmoniae levels and higher mortality. Treating RNAi-altered individuals with penicillin reversed this effect, successfully reducing S. harmoniae presence and increasing insect survival. Taken together, these findings demonstrate that S. harmoniae , a newly identified pathogenic bacterium carried by harlequin ladybirds, interacts with harmonine to confer an interspecies competitive advantage over native ladybird species in nonnative regions.